1990
DOI: 10.1002/pssb.2221600155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogenation of Defects at the Microcrystallite‐Glass Interface on the Nonlinear Optics of CdSe Microcrystallites

Abstract: BYThe nonlinear optical properties of 3D-confined semiconductor microcrystallites (MC) embedded in a glass matrix have been the subject of intense research in the last years. Having small MCs with nearly identical sizes a characteristic MC absorption line can be observed in the linear spectrum up to room temperature. Its halfwidth is essentially influenced by the MC size distribution because the MCenergy states depend sensitively on the MC size. In e.g. /1 to 31 the bleaching of the MC-absorption line at laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This indicates that the number of defects in our sample are few before irradiation and are created by irradiation, since the ESR signal is very weak before irradiation and increases after irradiation. On the other hand, the sample used by Woggon et al 13) may have contained many defects before irradiation, therefore they observed effects of hydrogenation in the sample before irradiation. These results indicate that glass composition plays an important role in the creation and annihilation of defects.…”
Section: )mentioning
confidence: 97%
See 1 more Smart Citation
“…This indicates that the number of defects in our sample are few before irradiation and are created by irradiation, since the ESR signal is very weak before irradiation and increases after irradiation. On the other hand, the sample used by Woggon et al 13) may have contained many defects before irradiation, therefore they observed effects of hydrogenation in the sample before irradiation. These results indicate that glass composition plays an important role in the creation and annihilation of defects.…”
Section: )mentioning
confidence: 97%
“…The effect of hydrogenation was investigated for CdSe-doped borosilicate glass before laser irradiation by Woggon et al 13) They measured the kinetics of induced transmission of the glass. They observed that the time constant of the fast component of the induced transmission for the hydrogenated sample is about twice that as before hydrogenation.…”
Section: )mentioning
confidence: 99%
“…In glasses, experiments are rare which give a direct comparison o f nonlinearoptics before and after a controlled interface modification. Changes o f the optical nonlinearity after controlled surface passivation by hydrogenation have been established for CdSe quantum dots in borosilicate glass matrix [48,49]. Over-barrier transitions o felectrons out ofthe quantum dot into the glass have been proven by measuring the thermo-stimulated luminescence o f semiconductor-doped glasses [50].…”
Section: Dynamics O F Trapping and Photodarkeningmentioning
confidence: 99%
“…The models presentedto explain the recombination dynamics of II-VI QDs embedded in organics or glasses can be classified in (i) three-or four-level systems without taking into account photodarkening [13,42] and (ii) modified three level systems including photodarkening by either the intensity-dependent activation o f a new trap state [43,44] or two-step absorption to excited states followed by the transfer into the glass matrix [45,48,49]. In addition, Auger processes have been considered in [47,50,52].…”
Section: Dynamics O F Trapping and Photodarkeningmentioning
confidence: 99%
See 1 more Smart Citation